Optically Bistable Macroporous Photonic Crystals Enabled by Thermoresponsive Shape Memory Polymers. Issue 11 (18th August 2015) - Fang, Yin; Leo, Sin‐Yen; Ni, Yongliang; Yu, Long; Qi, Pengxu; Wang, Bingchen; Basile, Vito; Taylor, Curtis; Jiang, Peng
Abstract : Macroporous photonic crystals with optically bistable states have been fabricated by using thermoresponsive shape memory polymers. The reversible transition between an ordered permanent state and a disordered temporary state results in tremendous changes in the appearance and the optical properties of the membranes.